The Effect of Supported Liquid Membrane and Liquid Membrane Phase on the Extraction Efficiency of Coal Gasification Wastewater - Jie, Yao; Ziwei, Du; Hong, You; Shuren, Yang; Biaoming, Li; Zhongwei, Wang; Agtmaal, Sjack van; Chunhui, Feng; Bangjun, Han (Journal of Membrane and Separation Technology, 2013)
The extraction and recovery of phenol from high concentration coal gasification wastewater has been investigated using polypropylene (PP) hollow fiber membranes and polyvinylidene fluoride (PVDF) hollow fiber membranes as supported liquid membrane and the mixture of extraction agent and paraffin as liquid membrane phase, with sodium hydroxide as stripping agent. The effect of the composition of the liquid membrane phase made of N-503-kerosene, tributyl phosphate (TBP)-kerosene or trialkyl phosphine oxide (TRPO)-kerosene on extraction efficiency has been studied. The supported liquid membrane give novel extraction result for the extraction of phenol from high concentration coal gasification wastewater when proper liquid membrane phases and liquid membrane support body materials are used in supported liquid membrane system. Under the operating conditions of waste water temperature at 20 ˚C pH at 8.4, waste water and stripping phase flow rate at 5 L/h, the supported liquid membrane using PP as supported liquid membrane and the extraction agent of TBP with volume proportion of 20% could operate continuously and stablely more than 24 hours and the extraction efficiency be 4% higher than that of PVDF-TBP supported liquid membrane systems. <!--[endif] -->